STUDENT EMPLOYABILITY AND COMMUNICATION DURING THE JOB RECRUITMENT PROCESS: THE OPINIONS OF STUDENTS AND EMPLOYERS - Šmitiņa, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The Career Centre of the University of Latvia undertook a comprehensive study regarding the issues of student employability and mutual communication with employers during the recruitment process. The study was conducted in two parts – 923 students from various higher education institutions in Latvia were surveyed during May-June 2015. The survey was used to inquire the current employment situation of the students of various study disciplines, determine the most popular types and choices of students in search for jobs and traineeship places, study the communication of the employers and given feedback to job seekers. The survey results outline the problems in mutual communication between the employers and employees and giving and receiving of feedback, as well as an explanation of the reasons for refusal of the job. In continuation of the study 84 employers were surveyed in spring 2017 regarding the experience of their company/institution in regard to employment of students, as well as communication with students as job seekers in the recruitment process. The outcome of the study show that employers are seeking students for a job position through job advertisement portals, but they try to recruit them also through social networks; in general they rate students as convincing during interviews, but also having excessive ambitions, expectations and not always an adequate appraisal of their own skills. The employers explain the problems noted by the students in regard to the employer communication during recruitment by being too busy, lack of time and a high number of applications per competition.